The role of HMOX1-mediated ferroptosis in blue light-induced damage to retinal pigment epithelium - Chunyi Ji; Yiqi Wang; Yahan Ju; Siwei Liu; Xirui Chen; Jiajing Wang; Na Sun; Zhimin Tang; Ping Gu; Jing Ji (Scientific Reports)
Abstract Currently, blue light irradiation is frequently encountered in daily life and is widely considered a high-risk factor for retinal damage. In particular, blue light-induced dysfunction and death of the retinal pigment epithelium (RPE) may ultimately contribute to irreversible vision impairment and even blindness. However, the underlying pathogenic mechanism and pathogenically targeted protection against blue light-induced RPE degeneration remain unclear. In this study, through sophisticated biochemical evaluation and high-throughput sequencing, the predominant pathological process during blue light-induced RPE degeneration was confirmed to be HMOX1-mediated RPE ferroptosis, which may be involved in the Nrf2–SLC7A11–HMOX1 hierarchy. Upon further knockdown of HMOX1 with si-HMOX1 or the HMOX1 inhibitor zinc protoporphyrin (ZnPP), specific inhibition of HMOX1 overexpression significantly suppressed RPE ferroptosis. In mice, treatment with ZnPP effectively rescued RPE degeneration and visual function. These results highlighted that HMOX1-mediated ferroptosis might be a potential target for protection against blue light-induced damage to RPE cells.